Faktor-Faktor Yang Mempengaruhi Kecurangan Dana Desa dengan Moralitas Sebagai Variabel Moderasi - Dewi Ayu Safitri; Siti Noor Khikmah; Yulinda Devi Pramita; Barkah Susanto; Wawan Sadtyo Nugroho (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
This research aims to empirically test the influence of the internal control system, village apparatus competence and organizational culture on preventing village fund management with morality as a moderating variable. The population of this study was all village officials in 20 village offices in Windusari District. The sampling technique in this research used purposive sampling, so that the research sample was 73 respondents. Respondents in this research were the village head, secretary, treasurer and planning officer. Data analysis to test the hypothesis used SPSS version 26. The results of this research show that the internal control system has a positive effect on preventing maintenance of village funds, while the competence of village officials has a negative effect and organizational culture has no effect on preventing maintenance of village funds. Furthermore, morality weakens the internal control system to prevent maintenance of village funds, while morality strengthens the competence of village officials to prevent maintenance of village funds. However, morality does not moderate organizational culture towards preventing conditions in managing village funds.